Feasibility Study of CHEAP: Digital Marketing App for Collaborative Batik MSMEs and Religious Sites - R Kurniawan Dwi Septiady; Alfa Yuliana Dewi (Value Added : Majalah Ekonomi dan Bisnis, 2025)
This study investigates the feasibility of the CHEAP ("Cempaluk Heritage App") as a digital marketing model to enhance cultural tourism appeal in Pekalongan Regency. The research addresses the challenge of sub-optimal cultural tourism promotion and untapped collaborative potential by examining the relationships between Perceived Application Quality, Cultural Tourism Appeal, and Visitor Intention to Visit/Purchase. Employing a mixed-methods approach, data was collected through surveys and interviews. A total of 46 participants, including potential tourists, batik MSME owners, and religious site managers, were selected using purposive sampling. Findings indicate that the proposed application is highly feasible, with strong positive perceptions of its quality directly enhancing the cultural tourism appeal. This heightened appeal, in turn, significantly increases visitors' intentions to engage with the sites and purchase local products, thereby fostering a sustainable collaborative model and strengthening Pekalongan's position as a cultural tourism destination.